Selective Laser Sintering of Metal‐Organic Frameworks: Production of Highly Porous Filters by 3D Printing onto a Polymeric Matrix. Issue 2 (19th February 2019) - Lahtinen, Elmeri; Precker, Rafaella L. M.; Lahtinen, Manu; Hey‐Hawkins, Evamarie; Haukka, Matti
Abstract: Metal‐organic frameworks (MOFs) have raised a lot of interest, especially as adsorbing materials, because of their unique and well‐defined pore structures. One of the main challenges in the utilization of MOFs is their crystalline and powdery nature, which makes their use inconvenient in practice. Three‐dimensional printing has been suggested as a potential solution to overcome this problem. We used selective laser sintering (SLS) to print highly porous flow‐through filters containing the MOF copper(II) benzene‐1, 3, 5‐tricarboxylate (HKUST‐1). These filters were printed simply by mixing HKUST‐1 with an easily printable nylon‐12 polymer matrix. By using the SLS, powdery particles were fused together in such a way that the structure of the printed solid material resembles the structure of a powder bed. The MOF additive is firmly attached only on the surface of partially fused polymer particles and therefore remains accessible to fluids passing through the filter. Powder X‐ray analysis of the printed object confirmed that printing did not have any negative impact on the structure of the MOF. CO2 ‐adsorption studies also showed that the activity of the MOF was not affected by the printing process. SLS offers a straightforward and easy way to fabricate tailor‐made MOF‐containing filters for practical applications. Abstract : Printing MOFs : In a new approach to metal‐organic framework (MOF) chemistry, selective laser sintering 3D printing was used to prepare macroscopic objects, in which MOF crystals are firmly anchored onto a polymeric support structure. The MOFs retain their functional properties throughout the 3D printing process.